An individualised approach to assess the sidestep manoeuvre in male rugby union athletes - Brown, S. R.; Hume, P. A.; Lorimer, A. V.; Brughelli, M.; Besier, T. F. (Journal of Science and Medicine in Sport, 2020)
Objectives: This study aimed to (1) quantitatively assess external knee abduction moments between legs, and (2) qualitatively assess anterior cruciate ligament injury risk between group mean and individual athlete data during the sidestep manoeuvre. Design: Descriptive cross-sectional study. Methods: Sixteen male academy-level rugby union athletes (20.4 ± 2.7 yr; 186.3 ± 9.1 cm; 99.1 ± 14.4 kg) performed three maximal effort sidesteps (>6.0 m s-1) on each leg. Three-dimensional motion analysis was used to obtain external knee abduction moments, wherein the two legs were separated by the preferred and non-preferred kicking leg. Quantitative comparisons were made between legs, while qualitative comparisons were made been group mean and individual athlete data. Results: When sidestepping on the non-preferred leg, athletes produced 25% greater knee abduction moments (ES = 0.43) and presented modified postural adjustments associated with injury risk (extended knee [ES = -0.26; -8%], more trunk lateral flexion [ES = 0.42; 17%] and more distance between the centre-of-mass and ankle-joint-centre of the stance leg [ES = 0.97; 11%]) compared to the preferred leg. Individually, only 9 out of 16 athletes presented a higher abduction moment in their non-preferred leg with individual asymmetries ranging between 2.2 and 47%. Conclusions: Nearly half of the athletes assessed in this study showed the potential to "slip under the radar" when using the group mean for assessment. When assessing athletes for anterior cruciate ligament injury risk factors, individual athlete data should be examined in conjunction with the group mean for a more holistic view of the data.